2000
DOI: 10.1046/j.1365-2036.2000.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth‐based quadruple therapy for Helicobacter pylori— a single triple capsule plus lansoprazole

Abstract: INTRODUCTIONHelicobacter pylori infection of the gastric mucosa is causally related to peptic ulcer disease and cure of this infection has therefore become the treatment goal in ulcer patients. 1±5 Several guidelines suggest that patients with non-ulcer dyspepsia should also be treated for the infection and a serological based`test and treat' strategy for young dyspeptics is gaining popularity. 3,4 Even though the indications for treatment are expanding, no consensus exists as to the most optimal therapy. Phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…It has been reported that quadruple therapy consisting of a similar combination of antibiotics and a proton-pump inhibitor has repeatedly been shown to be equally eff ective in spite of the presence of metronidazole resistance when the attention was given to the dose of metronidazole (e.g. 400 or 500 mg three times daily) and duration of therapy of approximately 14 days [47][48][49][50][51][52]. So, metronidazole-containing quadruple therapy may have overcome metronidazole resistance to some degree in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that quadruple therapy consisting of a similar combination of antibiotics and a proton-pump inhibitor has repeatedly been shown to be equally eff ective in spite of the presence of metronidazole resistance when the attention was given to the dose of metronidazole (e.g. 400 or 500 mg three times daily) and duration of therapy of approximately 14 days [47][48][49][50][51][52]. So, metronidazole-containing quadruple therapy may have overcome metronidazole resistance to some degree in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…This regimen was selected for development based on effectiveness, treatment duration, patient convenience, safety and cost. [16][17][18][19][20] The 'three-in-one' feature of this capsule was designed to increase acceptability and compliance, as the patient would need to take three of the four medications from the same bottle at the same times. This study was designed to assess the efficacy and safety of this regimen for the eradication of H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, however, the decrease of eradication rate of the standard triple therapy based on amoxicillin, clarithromycin plus a PPI, and the increasing prevalence of metronidazole or clarithromycin resistant strains have induced several authors to propose the quadruple therapy -based on metronidazole, tetracycline Fig (7), bismuth compounds and a PPI or ranitidine-even as first line option [76][77][78][79][80][81][82][83][84][85][86][87][88][89]. In literature several protocols are reported, decribing treatments lasting 7, 10 or 14 days, with different dosages of metronidazole, bismuth, tetracycline and PPI.…”
Section: Fluoroquinolones Quadruple Therapymentioning
confidence: 99%